Bioinformatics approach reveals the critical role of TGF-β signaling pathway in pre-eclampsia development. (September 2019) - Wu, Kejia; Liu, Fulin; Wu, Wanrong; Chen, Yurou; Zhang, Wei
Abstract: Background: Pre-eclampsia is a common pregnancy complication, affecting 5–8% of pregnancies worldwide. The specific mechanism of pre-eclampsia remains unclear. Objective: In this study, we aimed to apply bioinformatics approach to reveal related pathways or genes involving in the development of pre-eclampsia. Study design: The gene expression profiles of GSE9984 and GSE4707 were downloaded from the Gene Expression Omnibus database. Differentially expressed genes analysis was performed by GEO2R. The Database for Annotation, Visualization and Integrated Discovery (DAVID) was applied to analyze the functional enrichment, gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway of the differentially expressed genes. Gene Set Enrichment Analysis (GSEA) was conducted using the software GSEA v3.0. Protein-protein interaction (PPI) relationships were evaluated by the Search Tool for the Retrieval of Interacting Genes (STRING) and network visualization was constructed by the Cytoscape. Cell count kits-8 (CCK-8), transwell migration assay and tube formation assay were performed. Results: A total of 160 common differentially expressed genes were extracted. Transforming growth factor (TGF) beta signaling pathway was shown to be notable in the development of pre-eclampsia. ENG, a key gene of TGF-β signaling pathway, inhibited the proliferation, migration and invasion of both HTR-8/SVneo cells and human umbilical vein endothelial cells (HUVECs), and additionally suppressed the capillary formation of HUVECs. Conclusion: Bioinformatics approach combined with cell experiments in this study revealed that TGF-β signaling pathway was critical for the development of pre-eclampsia, and efficient biomarkers underlying this pathway need to be further investigated.